Pemanfaatan Fintech Pada UMKM Sidoarjo - Nadia Nur Lailatul Rifqiah; Wahyu Eko Pujianto (Universitas 45 Surabaya, 2023)
The purpose of this study is to find out how Fintech or Financial Technology can be used in digital applications Grab, Gojek, ShopeePay, Dana, Qris or GoPay in businesses or companies that use the latest technology services, facilitating the smooth operation of MSME and UKM companies in Sidoarjo. This research was conducted on Geprek SMEs using a qualitative data collection method with a descriptive approach, the purpose of which was to find out how business processes work with the help of an electronic payment system (Digital Wallet). The results of this study can be interpreted in such a way that the use of fintech e-wallets has a very positive and good effect and is very easy for users to understand.